PEMBERDAYAAN MASYARAKAT DALAM PERSPEKTIF AL QUR’AN - Tomi Hendra, M.Sos (IAIN Padangsidimpuan, 2017)
Empowerment is an effort to provide power (empowerment) or strengthening (strengthening) to the community. In other words, community empowerment is defined as the ability of individuals with the community in building community empowerment in question. Community empowerment is also interpreted as an attempt to change people's behavior in a better direction, so that the quality and welfare of their lives can gradually increase